B-langue : Développement du site d’apprentissage du français pour la compréhension orale du cours de français oral élémentaire - Bima Dewa Kusuma; Ria Fitrasih (Universitas Negeri Semarang, 2026)
This research focuses on the development of an online learning support to help students learn French, particularly listening skills, for students in the second-semester course of Français Oral Élémentaire at Universitas Negeri Semarang. This study aims to (1) provide the needs of beginning students in order to develop and learn French, especially listening skills, more easily, (2) design e-learning materials that are in line with the characteristics and needs of beginning students. The method used in this research is Sugiyono’s level 1 research and development. This research is an analysis of student needs, obtained through questionnaires distributed to second-semester students at Universitas Negeri Semarang. The questionnaire data is then used as website content. The score obtained in the data validation test for the website creation is 60%, indicating it is feasible. After the researcher's revision, the final score is 80%, indicating that it is entirely feasible. We can therefore say that the research carried out by the researchers is fully feasible and ready for use.